Ocena częstości występowania bólu głowy oraz objawów mu towarzyszących = Assessment of the frequency of the occurrence of headaches and associated with them symptoms - Kożuch, Katarzyna; Kozłowski, Piotr; Kozłowska, Magdalena; Ławnicka, Izabela (Journal of Education, Health and Sport, 2016)
Kożuch Katarzyna, Kozłowski Piotr, Kozłowska Magdalena, Ławnicka Izabela. Ocena częstości występowania bólu głowy oraz objawów mu towarzyszących = Assessment of the frequency of the occurrence of headaches and associated with them symptoms. Journal of Education, Health and Sport. 2016;6(5):11-20. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50903 http://ojs.ukw.edu.pl/index.php/johs/article/view/3503 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 04.05.2016. Ocena częstości występowania bólu głowy oraz objawów mu towarzyszących Assessment of the frequency of the occurrence of headaches and associated with them symptoms Katarzyna Kożuch1, Piotr Kozłowski2, Magdalena Kozłowska3, Izabela Ławnicka4 1Uniwersytet Medyczny w Lublinie 2Katedra Anatomii Człowieka, Zakład Anatomii Prawidłowej, UM w Lublinie 3Katedra i Klinika Neurologii, UM w Lublinie 4Katedra i Klinika Nefrologii, UM w Lublinie Uniwersytet Medyczny w Lublinie ul. W. Chodźki 1, 20-093 Lublin e-mail: piotr7176@gmail.com Streszczenie Celem pracy była ocena częstości występowania bólu głowy oraz objawów mu towarzyszących. W badaniu oceniono również poziom natężenia bólu oraz okoliczności pojawienia się dolegliwości bólowych oraz czas ich trwania i charakter bólu. Badaniem objęto 103 osób. Kobiety stanowiły 56,9% respondentów, natomiast mężczyźni 43,1%. Wiek ankietowanych zawierał się pomiędzy 18 a 75 lat. Badanie przeprowadzono w okresie od stycznia do marca 2016 roku metodą wywiadu standaryzowanego. Narzędziem użytym do zebrania danych, był autorski, anonimowy kwestionariusz. Kwestionariusz zawierał 43 pytania z możliwością jednokrotnego wyboru w tym trzy pytania z możliwością wielokrotnego wyboru. Przeprowadzono analizę statystyczną z wykorzystaniem testu chi- kwadrat. Wszystkie wartości w których p<0,05 uznano za istotne statystycznie. Wszyscy ankietowani skarżyli się na dolegliwości bólowe głowy. Ankietowani najczęściej (36,5%) wskazywali odpowiedź o występowaniu bólu głowy kilka razy w miesiącu. 39,4% ankietowanych odczuwa dolegliwości bólowe głowy o różnej porze dnia. Na pytanie dotyczące długości trwania dolegliwości bólowych ankietowani najczęściej (36,4%) wskazywali, że ból głowy trwa zazwyczaj około 1 godzinę. Respondenci istotnie statystycznie (p<0,05) częściej potrafili określić lokalizację bólu głowy. Ankietowani z podobną częstością wskazywali ból w okolicy skroniowej (27,7%) oraz w okolicy potylicznej (24,8%). Mężczyźni istotnie statystycznie (p<0,05) częściej odczuwają silniejszy ból głowy w porównaniu do kobiet. Najczęstszym objawem towarzyszącym dolegliwościom bólowym głowy była zmiana nastroju (66,3%, p<0,05). Blisko jedna trzecia ankietowanych odczuwa podczas napadu bólu głowy sztywność karku (28,7%), na nudności i wymioty skarży się blisko jedna czwarta ankietowanych (24,8%), podobnie często występują zawroty głowy (23,8%). Słowa kluczowe: ból głowy, migrena, napięciowy ból głowy, klasterowy ból głowy, pierwotny ból głowy, wtórny ból głowy. Abstract The aim of the study was to assess the prevalence of headaches and associated with them symptoms. The study also evaluated the severity, the circumstances of the emergence, the duration and the nature of pain. The study involved 103 people. Women accounted for 56.9% of the respondents, men- 43.1%. The age of the respondents was between 18 and 75 years of age. The study was conducted from January to March 2016 and implemented the standardized interview method. The tool used for data collection was an anonymous questionnaire. The questionnaire contained 43 single-choice questions and three multiple-choice questions. Statistical analysis was performed using chi-square test. All values for which p<0.05 were considered statistically significant. All respondents complained of headaches. Most of the respondents (36.5%) claimed to have headaches several times a month. 39.4% suffered from headaches at different times during the day. To the question regarding the duration of headache, respondents most often (36.4%) indicated that it usually lasted about 1 hour. Statistically significant respondents(p <0.05) were more likeky to precisely identify the location of headache. Respondents with similar frequency indicated pain in the temporal (27.7%) and occipital (24.8%) region. Statistically significant men (p <0.05) were more likely to experience stronger headaches compared to women. The most common symptoms associated with headaches were mood swings (66.3%, p <0.05). According to the respondents headache is usually accompanied by: neck stiffness (28.7%), nausea and vomiting (24.8%), and frequent dizziness (23.8%). Key words: headache, migraine, tension type headache, cluster type headache, primary headache, secondary headache.